The New Interpretation of the Photothermal Spectra of CdTe Samples After Different Surface Treatments - Jacek Zakrzewski; Mirosław Maliński; Mohammed Boumhamdi; Janusz Strzelecki; Karol Strzałkowski (Crystals)
This article presents new research on the surface condition of bulk crystal samples after the following stages of surface treatment: grinding, polishing, and etching. Furthermore, it shows how the surface condition affects the photothermal signal’s spectral amplitude and phase characteristics (PZE). A new theoretical interpretation of the photothermal spectra of CdTe samples after different surface treatments is proposed. We demonstrate that the piezoelectric method is susceptible to the surface condition, and it allows for the estimation of the thickness of surface-damaged layers of samples, and for the analysis of their thermal parameters. The roughness of surfaces obtained from the AFM pictures is estimated and compared to the photothermal results.